1990
DOI: 10.1113/jphysiol.1990.sp017908
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor function is regulated by phosphorylation in acutely dissociated guinea‐pig hippocampal neurones.

Abstract: SUMMARY1. Current mediated by GABAA receptors was examined in pyramidal cells acutely dissociated from the hippocampus of mature guinea-pigs. Current responses were measured using whole-cell voltage-clamp recordings. An internal perfusion technique was used to change the intracellular contents during recording.2. Application of GABA (100-300 /M) by short duration pressure pulses produced outward current responses at a holding potential of -10 mV. When recordings were made with intracellular solutions which did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
166
3
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(182 citation statements)
references
References 35 publications
12
166
3
1
Order By: Relevance
“…Along these lines, several studies have shown that GABA A receptor-mediated activity is regulated by phosphorylation. GABA A currents were decreased by Ͼ90% if cells were ATP-depleted (Chen et al, 1990), suggesting that a basal level of phosphorylation was required for maintenance of optimal GABA A receptor channel function. In addition, GABA A receptor conductance has been shown to be directly affected by PKA-mediated phosphorylation (Moss et al, 1992).…”
Section: Postsynaptic Effectsmentioning
confidence: 99%
“…Along these lines, several studies have shown that GABA A receptor-mediated activity is regulated by phosphorylation. GABA A currents were decreased by Ͼ90% if cells were ATP-depleted (Chen et al, 1990), suggesting that a basal level of phosphorylation was required for maintenance of optimal GABA A receptor channel function. In addition, GABA A receptor conductance has been shown to be directly affected by PKA-mediated phosphorylation (Moss et al, 1992).…”
Section: Postsynaptic Effectsmentioning
confidence: 99%
“…Recordings were made with pipettes (resistance 2-5 M⍀) filled with intracellular solution that contained (in mM): CsCl 140, HEPES 10, 1,2-bis(2-aminophenoxy)ethane-N,N,NЈ,NЈ-tetraacetic acid 10, pH 7.25; osmolarity, 300 -315 mOsm. Na 2 -ATP (4 mM) and MgCl 2 (2 mM) were included in the intracellular recording solution to support the process of protein phosphorylation, thereby preventing current rundown during a prolonged period of whole-cell recording (Chen et al, 1990). Currents were recorded under standard whole-cell voltage-clamp configuration using an Axopatch 1D amplifier (Axon Instruments, Foster City, CA).…”
Section: Methodsmentioning
confidence: 99%
“…This rundown involves a phosphorylationdephosphorylation process (Stelzer et al, 1988;Chen et al, 1990;Gyenes et al, 1994;Kaneda et al, 1995). Using whole-cell recordings, the currents elicited by GABA (100 M) were measured in neurons acutely dissociated from rat cortex (Fig.…”
Section: Function Of Gapdh-dependent Phosphorylationmentioning
confidence: 99%
“…In acutely dissociated neurons or in slices, maintenance of GABA A R function requires favorable conditions for phosphorylation, by an unknown endogenous kinase requiring only the addition of ATP in the intracellular milieu (Stelzer et al, 1988;Chen et al, 1990;Krupp and Feltz, 1993;Gyenes et al, 1994;Kaneda et al, 1995). Using purified GABA A R from bovine cerebral cortex, we and others have previously shown that this receptor-associated kinase activity is ␣1 specific (Sweetnam et al, 1988;Bureau and Laschet, 1995).…”
Section: Introductionmentioning
confidence: 99%